Pengaruh Motivasi Hedonik terhadap Impulsive Buying dan Compulsive Buying - Rini Anggriani; Lalu Jatmiko Jati; Raden Bagus Faizal Irani Sidharta; Baiq Dinna Widyasti (Target : Jurnal Manajemen Bisnis, 2022)
The changed in consumer’s buying behavior and the accompanying factors is an important issue and an interesting topic for further study by marketers and academics nowadays. In this case, impulsive buying behavior and compulsive buying in Lombok local teenagers that is using halal cosmetic become the subject of this study. This study aims to determine whether there is an influence of hedonic motivation on impulse buying and compulsive buying. The sampling technique used is the accidental sampling method with 200 samples. Data analysis used Structural Equation Modeling (SEM). The results showed that there is positive and significant influence and relationship between hedonic motivation and impulse buying. There is a positive and significant effect of impulsive buying on compulsive buying. There is no effect of hedonic motivation on compulsive buying.